Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Propertydan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Muzaiyanatul Ummah; Rahman Amrullah Suwaidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Property and real estate is a sector that has an important role in the economy in Indonesia. The purpose of this study is to determine the effect of the variables on profitability, leverage, and market ratio on stock prices in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The population of this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX), totaling 80 companies. The sampling technique chosen was by using a purposive sampling technique so that a sample of 50 companies was obtained. The data analysis method used is multiple linear regression analysis with the Statistical Package for the Social Sciences (SPSS) program. The results of the study show that a) Profitability has a significant positive effect on stock prices b) Leverage has no significant or negative effect on stock prices c) Market Ratio has a significant positive effect on changes in stock prices. Keywords: Stock Price, Profitability, Leverage, and Market Ratio